Determinants of Global Direct Investment in BRICS Economies: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Development of any economy or organization is depends on the availability of resources and mainly based upon financial resources. BRICS countries are the fast-developing economies in the world. BRICS as combined, account for more than a quarter of the world’s land area, 40% of the world’s population, and have a combined GDP (PPP) of US$ 20.39 trillion in 2011.This paper has tried to attempt an analysis of the possible determinants of Global Direct Investment in BRICS nations. This paper has divided in two part. First part deals with introduction, objective and methodology and second part explain the analysis and explanations and conclusion.